THEORETICAL ASPECTS OF MANAGING THE STRATEGIC POTENTIAL OF AN INNOVATION ORIENTED AGRICULTURAL ENTERPRISE - VORONKO-NEVIDNYCHA, Tetiana; SOBCHYSHYN, Vitaliy; BARANOVSKYI, Ivan; SVITLOVA, Anastasiia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article analyzes the main aspects of managing the strategic potential of an innovation-oriented agricultural enterprise. It is substantiated that as a result of the full-scale invasion, many Ukrainian enterprises are increasingly focused on survival, and development opportunities automatically fade into the background. The management of enterprises that operate effectively in the modern market recognizes the need for strategic management of activities based on forecasts of the direction of development, adjustment to constant changes in the external and internal environment. In this context, strategic management should rely primarily on human potential, adapt production activities to the needs of consumers, implement flexible rules and timely changes to respond to environmental challenges and achieve competitive advantage, and thus ensure stable operation and development for the future. It is proved that in the current conditions, the issues of managing the strategic potential of an innovation-oriented business entity in the agricultural sector related to digital transformation and innovation, environmental, safety and social responsibility are relevant. The author substantiates the factors that complicate long-term planning and require agricultural enterprises to adaptively manage, quickly adjust their strategies and use the potential for change. It is analyzed that rapid unpredictable changes affect the performance of an agricultural enterprise, while at the same time, to some extent, devaluing the effective value of existing classical management approaches. Instead, new technologies are emerging that radically change management techniques, tools, and means of influence. Their essence is as follows: development on the basis of functional efficiency, adaptive capacity, long-term vision, strategic flexibility in market formation and management; optimization of resource potential attraction, minimization of costs to maximize profitability and, most importantly, satisfaction of consumer needs and demands through the introduction of non-traditional and new ways to enter the market.